Pelapisan (Coating) pada Benih Cabai Merah Besar (Capsicum Annuum L) untuk Mencegah Penyakit Terbawa Benih - Anna Tefa; Aloysius Rusae; Febrianus Matnai (Fakultas Pertanian, Universitas Timor, 2019)
The development of red chili aims to increase the productivity of chili plants to meet increasing consumer demand every time year in line with the increasing number of population and the development of industries that require chili raw materials. This study aims to determine the dose of PGPR and anthracol fungicides to seed-borne diseases and to know the quality of seed physiology. Universitas Timor, Sasi subdistrict,subdistrict uses a completely randomized design of the first two factors of coating namely (C0) without, (C1) coating PGPR (C2) coating second factor anthracol fungicide are save period (P0) without storage (P1) first month retention, (P2) second month storage (P3) the third month environment Anova’s results showed that there was no interaction between the coating factor and the storage period for the maximum growing potential growth parameters and in the dava parameters germinating the vigor index of simultaneous growth in dry weight normal sprouts the incidence infection showed the interaction of Kefamenanu, north central Timor district.